Assessing honeybee vulnerability to residue-level acetamiprid and thermal stress under different nutritional conditions - Staron, Martin; Rajčáková, Ľubica; Planý, Matej; Abou-Shaara, Hossam (Journal of Plant Protection Research, 2026)
Honeybees, which serve as vital pollinators, are often exposed to agrochemicals as non-target organisms. Among these substances, the widely used insecticide acetamiprid is of particular concern, as it is frequently detected in bee products. Honeybees are also routinely subjected to multiple stressors simultaneously, including pesticide exposure and heat stress—the latter becoming increasingly problematic under ongoing climate change. Nutrition adds an additional layer of complexity to honeybee resilience, shaping how individuals respond to these concurrent stressors. In this study, the survival of nurse and forager honeybees was evaluated under two abiotic stressors—acetamiprid exposure at a residue level (52.78 µg kg⁻¹) and short-term heat stress (45°C for 2.5 h)—while providing bees with different dietary treatments: three types of honey and three commercial protein diets. Mortality of nurse bees was significantly higher in all acetamiprid-exposed groups than in the pesticide-free control, with honey-based diets providing better protection than protein-based diets. Regarding forager bees, mortality differed significantly between treatments, with buckwheat honey showing the lowest rates compared to protein diets and sugar candy. Age was a determining factor, as foragers exhibited higher mortality and lower consumption than nurses across treatments. Honey—particularly buckwheat —provided the most favorable outcomes, combining high consumption with reduced mortality under the study conditions. This study advances understanding of how nutrition can mitigate the impacts of multiple stressors on honey bees.